2008
DOI: 10.1097/gme.0b013e318054e29a
|View full text |Cite
|
Sign up to set email alerts
|

Histologic changes in the breast with menopausal hormone therapy use

Abstract: Objective-This retrospective study systematically compared mammographic density with histology in women receiving or not receiving menopausal hormone therapy (HT).Design-This study was approved by the institutional review board. Twenty-eight postmenopausal women using HT were matched with 28 postmenopausal women not using HT at the time of breast cancer diagnosis. Noncancerous tissue from mastectomy specimens was examined histologically to quantitate the content of fibrous stroma, ducts, and lobule types 1, 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 38 publications
7
20
0
Order By: Relevance
“…This result is in line with most of the previous studies [7,8,10,15,25]. Only one study, including benign breast tissue from 56 postmenopausal women found that high mammographic density was associated with increased levels of epithelial Ki-67 [11]. The assessment of cell proliferation can be challenging, as it is influenced by many factors, such as age and menstrual cycle.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is in line with most of the previous studies [7,8,10,15,25]. Only one study, including benign breast tissue from 56 postmenopausal women found that high mammographic density was associated with increased levels of epithelial Ki-67 [11]. The assessment of cell proliferation can be challenging, as it is influenced by many factors, such as age and menstrual cycle.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to other studies [7,8,11,15], we found no association between mammographic density and expression of epithelial hormone receptors ER and PR in any of our statistical models. Epidemiological studies have shown that mammographic density is not associated with any particular breast cancer sub-type [26,27], while some studies suggest that mammographic density is more strongly associated with ER-positive rather than ER-negative breast cancers [28,29].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As a result, it would be expected that DTI values would be the same across different FGT compositions because even in a predominantly fatty breast we are creating ROI's in the visually most fibroglandular region which stands to reason that it should be no different than a sample of a fibroglandular region in an overall extremely glandular breast. Our findings are additionally supported by histologic examinations that show that the number of ducts in a breast is constant and independent of overall mammographic density and that mammographic density is more a reflection of the amount of fibrous stroma [19]. …”
Section: Discussionsupporting
confidence: 70%